THE APPLICATION OF THREE-STEP TO INCREASE THE STUDENTS’ SPEAKING ABILITY - Mallombasi Mallombasi (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2012)
This research was intended to explain the students’ speaking accuracy and fluency through Three-Step Interview Method in class XI-2 of SMA Negeri 2 Bantaeng in the 2011/2012 academic year. This research used A Classroom Action Research (CAR). It had conducted in two cycles; each cycle consisted of four meetings. The subjects of this research were students in class XI-2 involved 40 students. Those consisted of 30 women and 10 men. The researcher took real data from the class to know the students’ speaking ability. The instruments of this research were speaking test and observation sheet in cycle I and in cycle II. The research findings indicated that the Three-Step Interview Method improved the students’ speaking ability covered students’ accuracy and fluency in class XI-2 of SMA Negeri 2 Bantaeng. It was indicated that there was an improvement of the students’ speaking ability from the diagnostic test to cycle I and from that to cycle II. The students’ diagnostic test of speaking ability was (5.47) and after gave action by using three-step interview method indicated that there was the improvement from diagnostic test to cycle I and from that to cycle II. The students’ speaking ability in cycle I was 63.00% and in the cycle, II become 76.50% and it was classified as good. While the standard target scores 70% one which was categorized well. From these findings, there was a significant improvement of the students’ speaking ability through Three-Step Interview Method. Based on the result finding the research concludes that Three-Step Interview Method can improve the students’ speaking ability.Keywords: Application, Three-Step, Increase, Speaking.